Study of changes in rs2283265 polymorphisms in dopamine receptor D2 and rs27072 in dopamine transporter gene (SLC6A3) in patients with attention-deficit hyperactivity disorder - Safavi, Parvin; Soleimani Farsani, Hossein; Farrokhi, Effat; Malekpour Tehrani, Afsaneh; Khoshdel, Nika; Khoshdel, Abolfazl (Iranian Journal of Child Neurology, 2022)
Objectives Attention-deficit hyperactivity disorder (ADHD) is one of the most common psychiatric disorders in children that lead to numerous complications. This study examined the changes in rs2283265 polymorphisms in the dopamine receptor D2 (DRD2) and rs27072 in the dopamine transporter gene (SLC6A3) in ADHD patients. Materials & Methods This descriptive-analytical study was performed on children aged 4-12 years with ADHD. In this study, 100 patients in the ADHD group (according to DSM-IV-TR criteria and diagnosed by interview by a child and adolescent psychiatrist) and 100 children in the control group (including patients referring to the pediatrician without hyperactivity) were enrolled. Two polymorphisms rs2283265 and rs27072 in two groups were comparatively investigated using PCR-RFLP method and restriction enzymes. Data were analyzed using SPSS 17. Results There was a significant correlation between gender and ADHD, and the disease was more common in boys (P=0.021). In this study, there was no significant relationship between ADHD types and frequency distribution of rs2283265 (DRD2) and rs27072 (SLC6A3) polymorphism genotypes (P<0.05). However, there was a significant correlation between distribution of rs2283265 (DRD2) and rs27072 (SLC6A3) polymorphisms and ADHD (P<0.05). Conclusion It seems that the changes in DRD2 and SLC6A3 genes are associated with ADHD, and study of these genes can be helpful in diagnosis and genetic screening.